KARAKTERISTIK UANG ELEKTRONIK DALAM SISTEM PEMBAYARAN - Rachmadi Usman (Universitas Airlangga, 2017)
Payment transactions with electronic money were conducted by transferring the fund electronically to merchant terminal, which would directly subtract the value of electronic money on electronic device managed by the owner. The characteristic of electronic money are as follows: to be deposited in advance to the issuer; the sum of money is electronically deposited in a particular medium, it can be card or other communication instrument; its function is as a non cash payment instrument to merchant not to the issuer of electronic money; and the sum of electronic money does not constitute saving product because it does not include in those guaranteed by Deposit Guarantor and it is not given any interest or reward. Electronic money is essentially cashless money, whose monetary value comes from the value of money deposited in advance to the publisher, then stored electronically in an electronic media such as server (hard drive) or chip card, which functions as a Non-cash payment instrument to the non-electronic issuer concerned. The monetary value of the electronic money is in electronic form (electronic value) obtained by redeeming a sum of cash or debiting his account in the bank and then stored electronically in electronic media in the form of a stored value card.